2020
DOI: 10.21203/rs.2.22827/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tracking Implementation Strategies in the Randomized Rollout of a Veterans Affairs National Opioid Risk Management Initiative

Abstract: Background: In 2018, the Department of Veterans Affairs (VA) issued Notice 2018-08 requiring facilities to complete ‘case reviews’ for Veterans identified in the Stratification Tool for Opioid Risk Mitigation (STORM) dashboard as high risk for adverse outcomes among patients prescribed opioids.. Half of facilities were randomly assigned to a Notice version including additional oversight. We evaluated implementation strategies used, whether strategies differed by randomization arm, and which strategies were ass… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…We draw from existing efforts to prospectively and retrospectively track and report implementation strategies within implementation research. Rogal and colleagues [33][34][35] surveyed implementation practitioners regarding their use of ERIC strategies to promote various health behaviors such as hepatitis C virus medication adherence. Importantly, Rogal and colleagues found that it was feasible to present stakeholders with the list of ERIC strategies and that stakeholders were able to reliably select the ones they used.…”
Section: Proposed Methods For Prospectively and Retrospectively Specimentioning
confidence: 99%
See 2 more Smart Citations
“…We draw from existing efforts to prospectively and retrospectively track and report implementation strategies within implementation research. Rogal and colleagues [33][34][35] surveyed implementation practitioners regarding their use of ERIC strategies to promote various health behaviors such as hepatitis C virus medication adherence. Importantly, Rogal and colleagues found that it was feasible to present stakeholders with the list of ERIC strategies and that stakeholders were able to reliably select the ones they used.…”
Section: Proposed Methods For Prospectively and Retrospectively Specimentioning
confidence: 99%
“…As the field of implementation science has matured, it has become quite clear that organizations often need to deploy many implementation strategies to successfully implement an intervention (e.g., [33,38]). For example, in Rogal's [33][34][35] aforementioned work, between 23 and 27 implementation strategies were used to support the health interventions. Reporting the implementation strategies used is only one component of a multi-item reporting checklist (e.g., item 9 of StaRI's 27 item checklist).…”
Section: Proposed Methods For Prospectively and Retrospectively Specimentioning
confidence: 99%
See 1 more Smart Citation
“…Academic detailing is an effective educational outreach strategy commonly used to impact care in this patient population by targeting uptake of evidence-based practice at the provider level [30,36]. Academic detailing [30,36] and other approaches [21,37] designed to promote uptake of evidence-based practice could benefit from this rapid, developmental approach to tailoring implementation strategies to fit the complex and dynamic interaction between the clinical innovation (M-OUD), recipients, and context. Our mixed methods analysis of 6-month outcomes helps us to understand whether implementation interventions and strategies can make meaningful change in facility metrics quickly to, ultimately, impact patient outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, many of the "evidence-based" implementation strategies that we have identified in similar projects are inherent to GTO (Table 2). These include providing facilitation, designating implementation leaders, site visits, developing an implementation blueprint, developing an interdisciplinary clinical team, and sharing lessons learned, audit and feedback, quality monitoring and adjusting practices accordingly, and tailoring while maintaining fidelity [21,47]. We anticipate that aim 1 may identify strategies that are not inherent to GTO.…”
Section: Aim 1 Analysismentioning
confidence: 99%